2017
DOI: 10.1002/pssr.201700182
|View full text |Cite
|
Sign up to set email alerts
|

Resistivity of Weyl semimetals NbP and TaP under pressure

Abstract: The resistivity of Weyl semimetals NbP and TaP has been investigated as a function of pressure and temperature. The behaviour of the resistivity as a function of pressure and temperature is closely correlated to the location of the Weyl points compared to the Fermi energy. The rapid increase of the resistivity in TaP and NbP under the application of 4.5 and 8.0 GPa is related with the shift of Weyl points, which affords a finite density of states near the Fermi energy. Specifically, we find that under pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…This signi fies the change in the electronic structure after ∼12 GPa. In another study by Einaga et al [27] on the same family of Weyl semimetals NbP and TaP, a similar trend was observed and the anomalous behavior of resistivity was associated with the decrease of density of states corresponding to Weyl points, located around the Fermi energy. The reason for the slight dif ference between the transition pressure in resistivity data and P Nb c might be due to the enhanced sensitivity of the former to changes in the electronic structure (to be discussed later) as compared to the phonon frequencies.…”
Section: Resultssupporting
confidence: 63%
“…This signi fies the change in the electronic structure after ∼12 GPa. In another study by Einaga et al [27] on the same family of Weyl semimetals NbP and TaP, a similar trend was observed and the anomalous behavior of resistivity was associated with the decrease of density of states corresponding to Weyl points, located around the Fermi energy. The reason for the slight dif ference between the transition pressure in resistivity data and P Nb c might be due to the enhanced sensitivity of the former to changes in the electronic structure (to be discussed later) as compared to the phonon frequencies.…”
Section: Resultssupporting
confidence: 63%
“…Electrical transport data provide, in addition to the information on the Fermisurface extracted from Shubnikov-de Haas (SdH) oscillations, access on the density and mobility of the charge carriers. So far, there have been only a few studies on the effect of pressure on the electrical-transport properties of the TaAs-family, NbAs, 26,27 NbP, [28][29][30] and TaAs. 31 In all these studies the crystalline and electronic structure are shown to be very stable.…”
Section: Introductionmentioning
confidence: 99%
“…For example, both the carrier doping and external pressure are known to engineer the Fermi surface of these compounds (e.g., Refs. 10,44,[48][49][50].…”
mentioning
confidence: 99%